THE IMPACT OF PEER MEDIATION TRAINING ONTOLERANCE TENDENCIES OF SECONDARY SCHOOL GRADE 5 STUDENTS AND THEIR VIEWS ON PEER MEDIATION (Third Sector Social Economic Review, 2019)
The purpose of this study is to determine the effect of peer mediation education on tolerance dispositions of 5th grade students. The study was performed using explanatory sequential mixed design. In quantitative stage, solomon experimental design was employed while fundemental qualitative research was adopted. The study group consisted of 5t grade students studying at a public school in Banaz town, Uşak province. “The Tolerance Disposition Scale” by Çalışkan and Sağlam (2012) was utilized during the experimental process. After the intervention, the data was obtained qualitatively via focus group interview. In quantitative analysis, percentile, and frequencies for descriptive statistics; dependent and independent sample t test, one way variance analysis, the Dunnet C test of multiple comparison tests were performed. In qualitative analysis, the data obtained by focus group interview was analyzed using content analysis. The findings of this study show that the effect of peer mediation education on tolerance dispositions of 5th grade students. As for comparison tests, experimental group both with and without pretest has significantly tolerance disposition more than other ones. The results in qualitative stage of the study explain that six themes obtained from ‘the Focus Group Interview A’; seven themes were derived from ‘the Focus Group Interview’. A and B interviews shared common themes: ""Values teaching, Skills teaching, Internal motivation, problem solving, and Otonomy"". They also revealed the evidence that 'concept teaching' theme is separeately derived from A group while 'Principles and Anger control' theme is obtained especially from B group.
Keywords: Peer mediation; Tolerance disposition; Social studies; Values education.